UNDERGRADUATE RESEARCH IS GETTING HARDER- NOT FOR PAKISTANI STUDENTS - Faize, Fayyaz Ahmad; Idrees, Samreen (European Scientific Journal, ESJ, 2014)
Undergraduate research has gained extensive popularity in the United States and western universities. However, it is still in infancy in the developing countries like Pakistan. The problem is that the universities are geared more towards teaching than research based activities. Majority of undergraduate students opt for a job after getting their degree but perform lower in their professional career due to little exposure with research based learning. Feeling the need for promoting a rigorous undergraduate research program in higher educational institutions in Pakistan, the researchers led a preliminary study to find the perception of undergraduate students about research-based engagements. The data were collected through a questionnaire. The perception of undergraduate students identified various interesting results. It was observed that the undergraduate students were highly motivated to be involved in research based activities. However, they were not satisfied with the research work. They students were hardly involved in any faculty-led project. The male and female students expressed their willingness to travel out of city for pursuing a research activity. The finding of this study is of great help to the researchers in introducing a program of action for promoting undergraduate research in Pakistan.